2022
DOI: 10.1152/ajplung.00447.2021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive channel Piezo1 is required for pulmonary artery smooth muscle cell proliferation

Abstract: Concentric pulmonary vascular wall thickening due partially to increased PASMC proliferation contributes to elevating PVR in patients with pulmonary hypertension (PH). While pulmonary vasoconstriction may be an early contributor to increasing PVR, the transition of contractile PASMCs to proliferative PASMCs may play an important role in the development and progression of pulmonary vascular remodeling in PH. A rise in cytosolic Ca2+ concentration ([Ca2+]cyt) is a trigger for PASMC contraction and proliferation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 167 publications
0
15
0
Order By: Relevance
“…Higher expression was detected in resistance arteries and lower expression in conduit arteries, with an increasing trend in the distal direction within each section ( Retailleau et al, 2015 ). Their function can also show regional differences due to, among others, the difference in pressure in the given section (systemic vs pulmonary circulations) ( Chen et al, 2022 ). Therefore, the extent of their contribution to the elevation of intracellular calcium concentration, and so, to the calcification can also vary ( Badin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression was detected in resistance arteries and lower expression in conduit arteries, with an increasing trend in the distal direction within each section ( Retailleau et al, 2015 ). Their function can also show regional differences due to, among others, the difference in pressure in the given section (systemic vs pulmonary circulations) ( Chen et al, 2022 ). Therefore, the extent of their contribution to the elevation of intracellular calcium concentration, and so, to the calcification can also vary ( Badin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that effective knockdown of Piezo1 attenuated the FBS-induced proliferation of human PASMC ( Maneshi et al, 2018 ) and inhibited the FBS-induced proliferation of human PASMC ( Liao et al, 2021 ). Also, previous study ( Chen et al, 2022 )have shown that Piezo1 is required for pulmonary artery smooth muscle cell proliferation. Expression of Piezo1 is increased in the pulmonary artery endothelial cells of patients with idiopathic pulmonary artery hypertension and experimental PH ( Wang et al, 2021 ) .…”
Section: Introductionmentioning
confidence: 80%
“…It has been reported that contractile and proliferative smooth muscles may have different Piezo1 expressions. 34) In this study, we mainly used cultured proliferative ASMCs. To test whether contractile ASMCs in vivo also express Piezo1, we compared the Piezo1 mRNA expression in freshly isolated ASMCs (P0, contractile phenotype), and cultured cells (proliferative phenotype) in the passage of 5 (P5) and P10.…”
Section: Yoda1 Activated Piezo1 Expressed In Asmcs Sincementioning
confidence: 99%